Localizing The Sacred: The Resilience of Sufism and The Vernacularization of Abdul Qodir Al-Jilani’s Manaqib in Banten - Ade Fakih Kurniawan; Denti Normayanti; Aprilia Musawamah (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2026)
The spread of Islam in the archipelago, especially in Banten, shows complex dynamics related to the role of Sufism and the vernacularization process. This article analyzes the process of appropriation and resilience of Sufism through the practice and the vernacularization of Wawacan Syeh text, which uses the text of the manaqib of Syekh Abdul Qadir al-Jilani in the local language (Banten dialect of Javanese) in Pegon script. Through a qualitative method, this study involves observation, vernacularized text analysis, and interviews with local communities. The results show that the vernacularization of Sufism not only makes Islamic teachings more accessible to the community since the early process of Islamization but also strengthens a moderate and inclusive religious identity. This process creates a synthesis between Sufi values ​​and local culture, so that Islamic teachings are not considered foreign, but become an integral part of the community's social life. The implications of these findings indicate that Sufism in Banten can survive and develop, prioritizing tolerance and respecting local culture/tradition. This research confirms that Islam in the archipelago, through Sufism, can survive the changing times and contribute to a harmonious social and religious life.